THE INFLUENCE OF ABILITY AND WORK MOTIVATION THE EMPLOYEE’S UNDERWRITING TO HAVE PERFORMANCE IN THE INSURANCE COMPANY IN JAKARTA - Hendra Gunawan (Business and Entrepreneurial Review, 2016)
In the Insurance Company, the performance of human resources plays major role in creating a good service, and it empirically linked to some factors. Currently these information regarding the factors influenced employee’s performance in Insurance Business. There were 108 respondents of employee participating from three Insurance Company, namely: PT. Asuransi Jiwa Sinarmas Jakarta, PT. Asuransi Takaful Keluarga Jakarta, PT. Asuransi Himalaya Pelindung Jakarta. The additional information gathered through focus group discussion with  Human Resources Managers on each insurance company. Data analyzed using the Simple and Multiple Regression. The dependant variable is Performance, while the independent variables are Ability and Motivation. The Ability variables was further devided into sub variables, namely: verbal comprehension, perceptual speed. The Motivation variable wasfurther divided into sub-variables namely: achievement, expectation, and  responsibility. The research found that Ability and Motivation have a significant effect on Performance. The Beta Coefficients for Ability and Motivation are 0,507 and 0,546 Respectively. The positive sign of Beta implies that Ability and Motivation can be used as measured of Performance. This research shows that the Motivation has a higher impact on Performance than the Ability. It’s mean the Employee’s ability should receive more attention when the Management has to plan to improve the Performance. Considering the object of this research is limited to three Insurance Company in Jakarta, so, the result of this research can’t be generalized for all Insurance Company. However, it’s to be hoped that the results will be useful for other insurance company managers in providing a preferable Human Resource Planning (HRP)